Two new species of eriophyid mites (Acari: Eriophyidae) from Malaysia - Yuan, Yan-Mei; Xue, Xiao-Feng (Zootaxa, 2019)
Two new species of the family Eriophyidae (Acari: Eriophyoidea) from Mount Trusmadi, Malaysia, are described and illustrated. They are Neodicrothrix grandcaputus sp. nov. on Stachyurus himalaicus (Stachyuraceae) and Latitudo asiaticis sp. nov. on Psychotria asiatica (Rubiaceae). Both of the two new species are vagrant on the lower leaf surface. No damage to the host was observed. In addition to the description, a key to species of Neodicrothrix is provided.